Occurrence of whales and dolphins in Pakistan with reference to fishers’ knowledge and impacts - Gore, M. A.; Kiani, M. S.; Ahmad, E.; Hussain, B.; Ormond, R. F.; Siddiqui, J.; Waqas, U.; Culloch, R. (J. Cetacean Res. Manage., 2023)
This paper reports the findings of a project (Cetacean Conservation Pakistan) launched in 2004 with a view to: (a) undertaking quantitative surveys to determine the variety and abundance of species present; (b) working with local fisher communities to collate local knowledge and promote public awareness; and (c) promoting a marine cetacean conservation strategy and measures. Boat-based surveys for live animals and shore surveys for beachcast specimens have confirmed the presence of twelve species of whale and dolphin. Among these bottlenose dolphins (Tursiops sp.) occur both inshore along the coasts of Sindh and Balochistan, and offshore in parts of Balochistan; these two populations possibly representing different sub-species. Indo-Pacific humpback dolphins (Sousa chinensis) are common inshore around the mouth of the Indus Delta and in large sheltered bays in Balochistan, where finless porpoise (Neophocaena phocaenoides) also occur. Spinner dolphins (Stenella longirostris) were observed in very large schools (up to 2,000) around the shelf edge in eastern Balochistan, as were Risso’s dolphins (Grampus griseus) in smaller numbers. Common dolphins (Delphinus capensis) were recorded even further offshore. There were two sightings of humpback whales (Megaptera novaeangliae), and one of a killer whale (Orcinus orca). Bryde’s whales (Balaenoptera edeni), sperm whales (Physeter macrocephalus) and Cuvier’s beaked whales (Ziphius cavirostris) were recorded only during beach surveys, while skeletal remains in institutions also supported the occurrence of blue whales (Balaenoptera musculus). Work with local fisher communities supported this picture of species distribution and provided information on threats to local cetaceans. These are principally occasional entanglement in fishing gear and opportunistic exploitation for use as food, as bait, as medicine or for other purposes. The project incorporated policy development and the preparation of a marine cetacean biodiversity action plan that included the listing of species in provincial conservation legislation, the designation of a marine protected area in Balochistan, the establishment of a national whale and dolphin conservation society, and trials of whale and dolphin watching as a means of raising public awareness and providing alternative economic value.